HGG-01. RADIATION INCREASES PRE-CLINICAL EFFICACY OF OLIG2 INHIBITOR CT-179 IN PEDIATRIC GBM. Issue 2 (22nd June 2018) - Lindsay, Holly; Du, Yuchen; Qi, Lin; Zhang, Huiyuan; Zhao, Sibo; Braun, Frank; Kogiso, Mari; Injac, Sarah; Sobieski, Mary; Stephan, Clifford; Alton, Gordon; Stein, Gregory; et al.
Abstract: BACKGROUND: Oligodendrocyte Lineage Transcription Factor 2 (OLIG2) is a pro-mitotic transcription factor highly expressed in glioma stem cells. We evaluated the pre-clinical efficacy of the OLIG2 inhibitor CT-179 in patient-derived orthotopic xenograft (PDOX) models of pediatric glioblastoma (pGBM). METHODS: Cells from 8 pGBM models were treated with single agent CT-179 (0-10 µM) as well as CT-179 (0-1 µM) plus radiation (XRT) (0-8 Gy). For in vivo drug testing, 105 pGBM cells were implanted into mice. After 1 week, treatment was initiated with vehicle, CT-179 (200 mg/kg via gavage every 4 days), XRT (2 Gy/day x 5 days), and combination CT-179/XRT. RESULTS: CT-179 inhibited cell viability in a time- and dose-dependent manner in all 8 pGBM tumors (IC50 0.03-10 µM). XRT potentiated the effects of CT-179 at low/moderate drug doses (0.03-1 µM). In vivo treatment was complicated by murine weight loss. Single agent CT-179 did not increase pGBM PDOX survival compared to vehicle (p=0.973) or XRT (p=0.262). However, the combination of CT-179 and XRT trended toward improved animal survival compared to vehicle (p=0.086). CT-179 and XRT combination treatment was significantly more effective at prolonging murine survival than single agent CT-179 (p<0.001). CONCLUSION: The OLIG2 inhibitor CT-179 demonstrated in vitro efficacy against numerous pGBM samples and a trend toward improved survival when combined with XRT in vivo in an aggressive PDOX model of pGBM. Further in vivo combinatorial testing in additional GBM models is planned through the Pediatric Pre-clinical Testing Consortium with drug administered every 5 days to prevent murine weight loss.